Effects of Invasive Species, Disease Outbreaks and Climate on Gorgonian Corals in the Tropical Eastern Pacific - Quintanilla Alcaide, Elena; Justus Liebig University Giessen (My University, 2021)
Gorgonian corals (Anthozoa, Octocorallia) play paramount roles in benthic communities. As long-lived and slow-growing species, gorgonians are particularly sensitive to environmental conditions and anthropogenic-related disturbances, being among the most vulnerable reef organisms. However, gorgonian responses to environmental conditions and the effects of abiotic and biotic threats to their populations are poorly understood in undisturbed marine areas. This lack of knowledge challenges the comprehension of gorgonian responses to human-associated disturbances. This doctoral thesis studies the effect of abiotic (i.e. local and global environmental conditions) and biotic (i.e. disease outbreaks and invasive species) factors affecting Pacifigorgia cairnsi sea fans, the most abundant coral and a key species surrounding the remote and pristine Malpelo Island, in the Colombian Tropical Eastern Pacific (TEP). In order to assess the health status of P. cairnsi and to understand whether these abiotic and biotic threats may represent long-term impacts to their populations, this thesis uses an integrative and multidisciplinary approach that includes phylogeography, metabarcoding, microbial ecology and demography. Major results suggest that, (1) P. cairnsi show high densities and their population size structures are driven by local hydrodynamics. Additionally, P. cairnsi growth rates are negatively affected by El Niño Southern Oscillation (ENSO) events and the ‘Necrotic Patch Disease’ (NPD) prevalence is low, while most of the colonies recovered. In addition, (2) the bacterial microbiome associated with the NPD affecting P. cairnsi populations behaves opportunistically and is likely in a state of microbial dysbiosis. Moreover, the confinement of the disease-related consortium to symptomatic tissues may facilitate colony recovery by tissue breakage. Finally, (3) the octocoral Carijoa riisei constitutes a fully invasive species in the TEP and might have been introduced from the Tropical Atlantic region, probably associated to international marine shipping. Overall, the conclusions include that P. cairnsi develop mature and healthy populations at Malpelo Island but threats, such as invasive species and ENSO events, may represent a long-term impact to these key benthic organisms. These valuable data and novel insights help to assess the vulnerability of these gorgonian corals in the absence of direct human-related disturbances. Moreover, this thesis provides crucial baseline data that will serve, in turn, as reference for future research aiming at understanding coral responses to direct anthropogenic pressures and the impact of global climate change on coral communities.
Keywords: Corals; Tropical Eastern Pacific; Invasive species; Coral disease; ENSO; Coral ecology; ddc:570